الإنتاج الفكري في مجال المكتبات والمعلومات بدليل دوريات الانتفاع الحر DOAJ: دراسة تحليله - العوامي عبدالكريم عبد الرحيم محمد; قناوي عبد الكريم محمد على (Tobruk University Journal of Social and Human Sciences, 2024)
This study examines open access journals in Library and Information Science in Directory of Open Access Journals (DOAJ). This study used descriptive and analytic approaches to understand nature of its growth and scientific values. The study also implemented general indications such as availability format, refereeing system, language and state to highlight the major trends. The study found that open access journals in library and information are increasing continuously and the most significant contribution were in 2013 and in 2017. English is the most widely used language and USA is the most contributing country in DOAJ. The study recommended that those interested in scientific research in Libya and the Arab region should launch an open access initiative in order to encourage researchers to significantly participate in DOAJ and raise the rates of Arab contribution to electronic content on the Internet.